RANCANG BANGUN SISTEM INFORMASI MANAJEMEN RESTRIBUSI PEDAGANG PASAR DESA KALIKOTES BERBASIS WEB - Cahyono, Damar Eko (Politeknik Sawunggalih Aji, 2025)
The village market is an instrument for utilizing the local economy with various types of potential. Utilization of this potential is primarily aimed at increasing the welfare and economic growth of village residents through developing their economic businesses. The market in Kalikotes Village is managed by BUMDES. BUMDES manages the market including collecting levies. The levy is paid every month. Retribution is a levy for services providing permits provided by the government to the public, whether individuals or certain bodies, based on location permits from the regional government, such as building construction and sales location permits in accordance with PP No. 10 of 2021. Market management wants all retribution transactions to be recorded. Recording retributions using an information system will be more recorded and accurate, so that the work can be completed efficiently and effectively.